Amplified Spontaneous Emission Realized by Cogrowing Large/Small Grains with Self‐Passivating Defects and Aligning Transition Dipoles. Issue 13 (29th April 2019) - Bai, Yujie; Qin, Jiajun; Shi, Lei; Zhang, Jia; Wang, Miaosheng; Zhan, Yiqiang; Zou, Han; Haacke, Stefan; Hou, Xiaoyuan; Zi, Jian; Hu, Bin
Abstract: This paper reports an amplified spontaneous emission (ASE) initiated by intrinsically passivating grain boundary defects and aligning transition dipoles in polycrystalline perovskite (MAPbBr3 ) films. The method is developed by using concurrently occurring fast and slow growths to attach small grains on surfaces of large grains toward low‐threshold ASE. This materials processing utilizes one‐step solution method of mixing two MAPbBr3 precursor (PbBr2 ‐based and Pb(Ac)2  · 3H2 O‐based) solutions to control two subsequent growths: quickly growing large grains followed by slowly growing small grains, leading to unique emitting centers from large grains and self‐doping agents from small grains. With this design, spectral narrowing phenomenon is observed from the large grains with the full width at half maximum decreasing from 21 to 4 nm when the pumping fluence is increased from 2 to 10 µW, generating an efficient ASE. Concurrently, the observed ASE shows a linear polarization reaching 21.1%, indicating that the transition dipoles in large grains are linearly polarized with coherent interaction. Therefore, this processing strategy presents a unique method to intrinsically passivate grain boundary defects and align transition dipoles toward developing ASE by attaching small grains (serving as passivation agent) to the surfaces of large grains (functioning as light‐emitting centers). Abstract : Amplified spontaneous emission (ASE) is realized from linearly polarized light‐emitting states with coherent interaction by using concurrently occurring fast and slow crystallizations to attach nanoscale small grains to the micrometer‐scale large grains in polycrystalline perovskite (MAPbBr3 ) films. With one‐step solution processing method, small and large grains function as dopant agents and light‐emitting centers through self‐passivation mechanism occurring at grain boundaries toward developing ASE.